The Clinical Significance of a Low Percentage of Mature Oocytes Retrieved Using Common Ovarian Stimulation Protocols. - Wiesak, Teresa; Milewski, Robert; George Somkuti, Stephen (Journal of Fertility Biomarkers, 2017)
The objective of this study was to investigate whether percentage of mature oocytes retrieved from ovaries stimulated with long agonist or multi-dose antagonist protocols affect the implantation, clinical pregnancy and live birth of ICSI (Intracytoplasmic sperm injection) cycles. The 654 cycles of agonist (long lupron) and 610 cycles of multi-dose flexible antagonist (antagon) were analyzed after stratification according to the percentage of the mature oocytes retrieved. The clinical pregnancy of the groups with less than 30 % mature oocytes retrieved, both antagonist and agonist protocol was statistically lower (at least p< 0.05) compared to the groups with more than 30% mature oocytes retrieved. In the agonist protocol, the implantation and live births for this group were significantly (p<0.009) lower than in the group with ≥70% mature oocytes retrieved. The live births in groups with more mature oocytes retrieved (30-69% and ≥70 %) of the antagonist protocol were lower (22.2% vs. 35.9% and 23.9% vs. 41.5%, p<0.0001, respectively) compare to the agonist protocol. The results of our study showed that a very low percentage of mature oocytes retrieved impacts the clinical outcome of antagonist and long agonist protocols.
Keywords: Pregnancy; Live births; Maturity of oocytes; GnRH- antagonist; GnRH - agonist.